Stab resistant body armour - Horsfall, Ian (Cranfield University, 2000)
There is now a widely accepted need for stab resistant body armour for the police in the UK. However, very little research has been done on knife resistant systems and the penetration mechanics of sharp projectiles are poorly understood. This thesis explores the general background to knife attack and defence with a particular emphasis on the penetration mechanics of edged weapons. The energy and velocity that can be achieved in stabbing actions has been determined for a number of sample populations. The energy dissipated against the target was shown to be primarily the combined kinetic energy of the knife and the arm of the attacker. The compliance between the hand and the knife was shown to significantly affect the pattern of energy delivery. Flexibility and the resulting compliance of the armour was shown to have a significant effect upon the absorption of this kinetic energy. The ability of a knife to penetrate a variety of targets was studied using an instrumented drop tower. It was found that the penetration process consisted of three stages, indentation, perforation and further penetration as the knife slides through the target. Analysis of the indentation process shows that for slimmer indenters, as represented by knives, frictional forces dominate, and indentation depth becomes dependent upon the coefficient of friction between indenter and sample. Analytical models are demonstrated to provide a reasonable estimate of energy absorption during and after penetration for a wide variety of knives and armour materials. The key armour parameters are shown to be the frictional interaction with the blade and the strength of the target material. The performance of knife blades is shown to increase with increasing sharpness, slimness, and surface finish. No single knife design performs best against all types of armour, and no single armour is best against all knife blades.